The Effect of User Experience on Donation Interest through The Digital Wallet Applications - Apriliani Dwi Tandy; Maulana Syarif Hidayatullah (Universitas Pembangunan Nasional Veteran Jakarta, 2021)
AbstractTechnological developments that have penetrated the financial sector have provided convenience and comfort for the public in digitally transacting, including in donating. The condition of the Covid-19 pandemic has also required people to work from home, so that donation transactions made through digital applications are very relevant to be implemented. This study aims to see the effect’s comparison of user experience on the donation interest through the digital wallet applications of Gopay, OVO, DANA, and LinkAja in teachers and staffs who work at the Vocational High School 1 Jambi City. The method used is the non-probability sampling with a sample size of 118 respondents. The measurement of user experience in this study used simplicity, security, and convenience factors. Analysis of comparative used the Kruskal Wallis H test with SPSS version 25 software. The results showed that there were differences in simplicity, security, convenience and user experience between the interest in donating users through the digital wallet application of Gopay, OVO, DANA, and LinkAja. This study is based on the author’s thoughts so that the originality can be responsible.AbstrakPerkembangan teknologi yang merambah sektor keuangan, telah memberikan kemudahan dan kenyamanan bagi masyarakat dalam bertransaksi secara digital, termasuk dalam berdonasi. Kondisi pandemi Covid-19 juga telah menuntut masyarakat untuk beraktivitas dari rumah, sehingga transaksi berdonasi yang dilakukan melalui aplikasi digital sangat relevan untuk diterapkan. Penelitian ini bertujuan untuk mengetahui perbandingan pengaruh user experience terhadap minat berdonasi melalui aplikasi dompet digital Gopay, OVO, DANA, dan LinkAja pada Guru dan Staf yang bekerja di SMK Negeri 1 Kota Jambi. Metode yang digunakan adalah metode non-probability sampling dengan jumlah sampel sebanyak 118 responden. Pengukuran user experience pada penelitian ini menggunakan faktor kemudahan, keamanan, dan kenyamanan. Analisis perbandingan menggunakan uji Kruskal Wallis H dengan software SPSS versi 25. Hasil penelitian menunjukkan bahwa terdapat perbedaan kemudahan, keamanan, kenyamanan, dan pengalaman pengguna antara minat berdonasi pengguna aplikasi dompet digital Gopay, OVO, DANA, dan LinkAja. Artikel ini didasarkan pada pemikiran penulis sehingga dapat dipertanggungjawabkan keasliannya.